2018
DOI: 10.1111/ijfs.13932
|View full text |Cite
|
Sign up to set email alerts
|

Ropy exopolysaccharide‐producing Bifidobacterium longum YS108R as a starter culture for fermented milk

Abstract: Bifidobacteria are generally inferior compared to traditional starter lactic acid bacteria (LAB) in terms of fermentation properties. The results of this study showed that the use of a ropy EPS producing strain Bifidobacterium longum YS108R during fermentation improved the physicochemical properties of fermented milk, including decreased whey syneresis and increased water-holding capacity and apparent viscosity, however, another non-ropy EPS producing strain B. longum C11A10B did not exert such effects. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(42 reference statements)
2
4
0
Order By: Relevance
“…Decreasing pH and disulfide bonds can lead to casein aggregation and result in gel formation [22]. These results are consistent with those of Yan et al [7], who found that viscosity increased when Lactobacillus bulgaricus, Streptococcus salivarius subsp. thermophilus, and Bifidobacterium longum were used together.…”
Section: Viscositysupporting
confidence: 90%
See 1 more Smart Citation
“…Decreasing pH and disulfide bonds can lead to casein aggregation and result in gel formation [22]. These results are consistent with those of Yan et al [7], who found that viscosity increased when Lactobacillus bulgaricus, Streptococcus salivarius subsp. thermophilus, and Bifidobacterium longum were used together.…”
Section: Viscositysupporting
confidence: 90%
“…thermophilus, and Bifidobacterium longum together has higher viscosity than separately fermented, respectively. Additionally, specific exopolysaccharide (EPS) producing bifidobacterial could improve the quality of fermented milk products, including physicochemical properties, as well as endowing products with health benefits [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the highest apparent viscosity in all stirred yogurts was 1.7 Pa.s in Guénard-Lampron’ study [ 42 ], which was less than that of this study. Differences in apparent viscosity of yogurt made from EPS-producing strains could be attributed to differences in the number and the molecular characteristics of EPS and their ability to interact with proteins [ 43 ]. Kumar [ 44 ] showed that the apparent viscosity of dairy products decreased when the speed increased during agitation.…”
Section: Resultsmentioning
confidence: 99%
“…Apparent viscosity was determined according to Yan et al [ 39 ] with modification. The apparent viscosity was measured with an NDJ-5S digital viscometer (Shanghai Drawell Scientific Instrument Co., Ltd., Shanghai, China) using spindle No.…”
Section: Methodsmentioning
confidence: 99%